Fecundidade de Callinectes danae Smith, 1869 (Crustacea, decapoda, portunidae) na região de Ubatuba(SP), Brasil - Costa, Tânia Marcia; Negreiros-Fransozo, Maria Lúcia [UNESP] (My University, 1996)
The fecundity of C. danae in Ubatuba (SP) region was analized. The swimming crabs were collected by trawl during two consecutive years. Only females carring early developmental stage eggs were used in this work. The ovigerous females mean size based on the carapace width, except the lateral teeth, was 21.5 ± 90 mm. The fecundity obtained from 29 ovigerous females varied from 363,660 to 826,638 eggs.
Fecundity of Callinectes danae Smith, 1869 (Crustacea, decapoda, portunidae) in Ubatuba region (SP), Brazil
Keywords: Brachyura; Callinectes danae; Eggs; Fecundity; Portunidae